Rupture of the spleen due to blunt thoracoabdominal trauma caused by a hunting weapon - Cazabán Perossio, Luis Alberto (Cirugía del Uruguay, 2020)
A case of a visceral lesion from contusion as a result of a non-penetrating gushot woud, of an infrequent production mechanism, is reported upon.